When the shape of the glass influences the flavour associated with a coloured beverage: Evidence from consumers in three countries - Wan, X; Woods, A; Seoul, K; Butcher, N; Spence, C (Elsevier, 2015)
We report a study designed to investigate the effect of the shape of the glass on colour-flavour associations in 300 participants from the UK, India, and South Korea. Participants viewed online photographs of red, green, yellow, blue, orange, and brown beverages presented in a water, wine, or cocktail glass, and indicated the first flavour or drink that came to mind from a list of 24 flavour options. The results revealed significant cross-cultural differences in terms of the flavour expectations that were elicited by viewing each of the coloured drinks. Furthermore, the crossmodal associations for the green, yellow, and orange drinks were also found to be influenced by the shape of the glass in which the drink was presented. These findings demonstrate how contextual factors (the shape and/or type of glass) can influence the crossmodal associations that exist between colour and flavour across different cultural backgrounds. Our results further highlight the importance of considering the appropriateness of the glassware in which a drink is presented (e.g., in advertising and in any images shown in product packaging). © 2014 Elsevier Ltd.